THU0166 Safety Profile of Baricitinib in Patients with Active RA: An Integrated Analysis. (15th July 2016) - Smolen, J.; Genovese, M.; Takeuchi, T.; Hyslop, D.; Macias, W.L.; Rooney, T.P.; Chen, L.; Dickson, C.; Riddle, J.; Cardillo, T.; Winthrop, K.
Abstract : Background: Baricitinib (bari; an oral JAK 1/JAK 2 inhibitor) is in development for patients (pts) with active RA. Objectives: To assess the safety of bari in pts with active RA across 8 completed studies (4 Ph3, 3 Ph2, 1 Ph1b) and 1 ongoing long-term extension (LTE) study. Methods: Primary safety analysis was based on 6 studies with bari 4 mg QD and placebo (PBO) arms and dose response assessments on 4 studies with bari 2 and 4 mg QD and PBO arms. In addition, the all-bari RA set included all patients exposed to any bari dose. 2 studies contained active comparators. Results: 3464 pts were exposed to bari (4214 pt-yrs (PY); 2166 pts (62.5%) >1 yr; 467 (13.5%) >2 yrs). In controlled periods of the program, no increases in deaths, AEs leading to study drug discontinuation, malignancies, MACE, or serious infections were seen for bari vs PBO/active treatment. Herpes zoster was reported more frequently for bari vs PBO. In randomized, controlled periods of the program, TB was reported in 2 pts: 1 bari 4 mg, 1 adalimumab; in uncontrolled periods, 6 TB events were reported (bari 4 mg: 2 with incomplete TB screening, 3 without organism confirmed). All TB occurred in endemic areas. Two GI perforations were reported (0.05/100 PY). No confirmed opportunistic infections were reported. Bari treatment has been associated with changes in selected hematology/clinical chemistry analytes; few patients (<1%) discontinued due to abnormal lab results. There was no observed increased risk over time for the above outcome measures with longer exposure. Conclusions: In the context of reported efficacy, 1, 2 bari had an acceptable safety profile in pts with moderate-to-severe active RA. References: Dougados M. Ann Rheum Dis. 2015;74(S2):79. Taylor PC. Arthritis Rheumatol. 2015;67(suppl 10). Disclosure of Interest: J. Smolen Grant/research support from: AbbVie, Janssen, Eli Lilly and Company, MSD, Pfizer, Roche, Consultant for: Abbvie, Amgen, Astra-Zeneca, Astro, Celgene, Celtrion, Glaxo, ILTOO, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, UCB, M. Genovese Grant/research support from: AbbVie, Astellas, Eli Lilly and Company, Galapagos, Pfizer, Vertex, Consultant for: AbbVie, Astellas, Eli Lilly and Company, Galapagos, Pfizer, T. Takeuchi Grant/research support from: Chugai Pharmaceutical Co, . Ltd, Eli Lilly and Company, Consultant for: Eli Lilly and Company, D. Hyslop Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, W. Macias Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, T. Rooney Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, L. Chen Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, C. Dickson Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, J. Riddle Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, T. Cardillo Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, K. Winthrop Grant/research support from: BMS, Pfizer, Consultant for: BMS, Pfizer, Eli Lilly and Company, Abbvie, Galapagos